Adoption and economics of silver barb (Puntius gonionotus) culture in seasonal water in Bangladesh. - Gupta, Modadugu V.; Rab, M. Abdur (Manila, Philippines ICLARM, 1994)
ICLARM Tech. Rep. 41
Keywords: Aquaculture economics; Technology assessment; Fish culture